House Rental Management System - Misyam, Mohd Rafiq; Selamat, Norhanim (Applied Information Technology And Computer Science, 2021)
House is a place for gathering of human beings that can improve the quality of life for human economically and socially. However, to reduce the cost of the expenses for a person, the person needs to rent a rental house first rather than continue to buy the house. Thus, the person who wants to rent a house must follow the price that has been measured by House Index Price (HPI) and must follow all the requirements set by Malaysia that is to make a contract between the owner and the tenant. There are some problems from the current process which is the tenants difficult to know which are the rental house that can be rented at the desired location. The tenants do not know how to pay the rental payment using online and there is no contract agreement between the tenants and the landlord. Motivated by this problem, rental house management system is developed to manage all matters involved in renting a house. With the development of this system, users only need to login into the system to book the rental house that available in the system. The methodology that used in developing this system is prototyping. The programming languages that used in this system are Hypertext Preprocessor (PHP) and Hypertext Mark-up Language (HTML) and MySQL database. It is hoped that this system is successfully developed and can facilitate tenants and owners in managing rental house.